F‐Spondin Inhibits Differentiation of Clastic Precursors via Lipoprotein Receptor–Related Protein 8 (LRP8). Issue 3 (1st March 2015) - Oka, Hiroko; Kitagawa, Masae; Takata, Takashi
Abstract : Background: F‐spondin, known to be a secreted neuronal glycoprotein, is highly expressed on the tooth root surface. The authors previously reported that F‐spondin is one of the specific markers of cementoblasts in periodontal tissue. In chronic periodontitis, significant cemental resorption rarely occurs on the root side, although alveolar bone resorption by osteoclasts is one of the major pathologic changes. Thus, it was hypothesized that secretory F‐spondin from cementoblasts might be involved in differentiation of clastic cells on the root surface. The authors studied effects of secretory F‐spondin from F‐spondin–expressing cells and its pathway on receptor activator of nuclear factor‐κB ligand (RANKL)‐mediated differentiation of clastic cells. Methods: Osteoclast precursors were used in this study. With a chamber assay, the authors examined effects of secretory molecules from F‐spondin–expressing cells of transgenic mice on RANKL‐induced clastic cell differentiation. Results: Secretory molecules from F‐spondin–overexpressing cells significantly inhibited the RANKL‐mediated tartrate‐resistant acid phosphatase (TRAP)‐positive cells from primary progenitor cells with the chamber system. F‐spondin suppressed RANKL‐mediated nuclear factor of activated T‐cells, cytoplasmic 1 (NFATc1); TRAP; cathepsin K; and dendritic cell–specific transmembrane protein (DC‐STAMP) expression in the cells. The suppressive effect of F‐spondin on RANKL‐induced differentiation of clastic cells was partially blocked by knockdown of low‐density lipoprotein receptor–related protein 8 (LRP8). Conclusions: These findings indicate that secretory factors from F‐spondin–expressing cells, including F‐spondin, downregulate differentiation of clastic precursors. Moreover, F‐spondin inhibits RANKL‐mediated differentiation of clastic cells partially via LRP8. It is suggested that secretory F‐spondin may act protectively from cemental resorption partially via LRP8 in periodontal tissue.